2007
DOI: 10.1016/j.jns.2006.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Mild head injury—a close relationship between motor function at 1 week post-injury and overall recovery at 3 and 6 months

Abstract: Based on previous findings of impaired eye and arm motor control after mild closed head injury (CHI), this study examined whether early eye and arm motor function, and the level of post-injury cerebral dysfunction manifested in motor control, relates systematically to recovery at 3 and 6 months after mild CHI. At 1 week post-injury, we assessed oculomotor function, upper-limb visuomotor performance, and cognitive status in 37 mild CHI patients. Re-examination at 3 and 6 months determined outcome in terms of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…This may be owing to the small number of saccades elicited (44 per patient), and certainly to the diluting effect of comparing patient and control groups rather than using data from before and after concussion in individual subjects (individual latency distributions are idiosyncratic but highly reproducible). Indeed, in the follow-up study,13 they found a close relationship between mean latency within 1 week and level of self-perceived recovery within the first 6 months after injury.…”
Section: Discussionmentioning
confidence: 85%
“…This may be owing to the small number of saccades elicited (44 per patient), and certainly to the diluting effect of comparing patient and control groups rather than using data from before and after concussion in individual subjects (individual latency distributions are idiosyncratic but highly reproducible). Indeed, in the follow-up study,13 they found a close relationship between mean latency within 1 week and level of self-perceived recovery within the first 6 months after injury.…”
Section: Discussionmentioning
confidence: 85%
“…In a broader scope, eye movements and the upper limb have been sensitive markers of cerebral injury when examining visuomotor skill (131). Additionally, function of the eye and arm following acute ABI can predict outcomes in the subacute and chronic stages following injury, with greater performance when compared to self-reported health status or neuropsychologic assessment (3, 132, 133). These prognostic capabilities extend to the identification of individuals who may require more comprehensive intervention or who are poor responders (6, 7).…”
Section: Discussionmentioning
confidence: 99%
“…More broadly, eye movements and visuomotor skill of the upper limb have been sensitive markers of cerebral injury (245). Taken further, eye and arm function following acute ABI has demonstrated good predictive capacity for outcomes in the subacute and chronic stages following injury with superior performance when compared to health status on self-report or based on neuropsychologic assessment (1, 246, 247). These prognostic capabilities have also enabled the identification of individuals who are poor responders or those who may require more aggressive intervention (248, 249).…”
Section: Impairment Of the Visuomotor Systemmentioning
confidence: 96%